2020
DOI: 10.1016/j.commatsci.2019.109344
|View full text |Cite
|
Sign up to set email alerts
|

Predicting magnetization of ferromagnetic binary Fe alloys from chemical short range order

Abstract: Among the ferromagnetic binary alloys, body centered cubic (bcc) Fe-Co is the one showing the highest magnetization. It is known experimentally that ordered Fe-Co structures show a larger magnetization than the random solid solutions with the same Co content. In this work, based on density functional theory (DFT) studies, we aim at a quantitative prediction of this feature, and point out the role of the orbital magnetic moments. Then, we introduce a DFT-based analytical model correlating local magnetic moments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Then the magnetization decreases again because Fe moments increase at a slower rate (0.06 μ B per 10% Ni [33]) and the magnetic dilution effect becomes dominant again. Please note that the Fe and Ni moments do not necessarily follow the trend of the magnetization and have local-composition dependence [44]. Indeed, it is found that the local chemical environment has a large impact on the magnetic moments than the local atomic volumes [33].…”
Section: B Magnetic Propertiesmentioning
confidence: 99%
“…Then the magnetization decreases again because Fe moments increase at a slower rate (0.06 μ B per 10% Ni [33]) and the magnetic dilution effect becomes dominant again. Please note that the Fe and Ni moments do not necessarily follow the trend of the magnetization and have local-composition dependence [44]. Indeed, it is found that the local chemical environment has a large impact on the magnetic moments than the local atomic volumes [33].…”
Section: B Magnetic Propertiesmentioning
confidence: 99%
“…13 (d). This result may be associated to the electronic properties of Fe and Co atoms in pure and Fe-Co systems where Co has an essentially saturated magnetism, while Fe can still enhance its magnetism in the presence of excitations, by for example, shifting down the highest peak in the majority-spin states of Fe atoms towards the Fermi level in Fe-Co structures [43].…”
Section: The Effect Around the Zero-field Magnetic Transition At A Gi...mentioning
confidence: 99%
“…( 1) corresponds to the Heisenberg model with ij J being the exchange-coupling parameter for the magnetic moments of ith and j-th atoms. However, unlike the traditional Heisenberg model in which the amplitude of an atomic moment is fixed, the magnetic part of the model (1) takes into account the longitudinal spin fluctuation due to the effect of the local environment as observed by the DFT calculations [43],…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This behaviour suggests that Fe-rich (Mn,Fe,Co) 1.95 (P,Si) alloys might exhibit a similar magnetic behaviour as the Fe-Co alloys. Various studies show that the average magnetic moment of Fe-Co alloy reaches the highest value for a small Co content (20-25 at.%) before a decrease is observed [36][37][38]. The reason responsible for a rapid increase in M s for a small Co doping is complex and is related to changes in the magnetic moment and electronic structure [39].…”
Section: Magnetic Propertiesmentioning
confidence: 99%